2019
DOI: 10.1111/pre.12403
|View full text |Cite
|
Sign up to set email alerts
|

Differential heavy metal sensitivity in seven algal species from the NIES culture collection based on delayed fluorescence assays

Abstract: Seafloor massive sulfide (SMS) deposits are the target of available metallic resources. The toxic impacts of leachable metals from hydrothermal ore by mining operations in marine environments are a concern. However, ecotoxicological knowledge about marine algae, and particularly open ocean species, is still limited. Here, we evaluated the toxic effects of three leachable metals (i.e. Zn, Cu, and Pb) on seven marine algae, including cyanobacteria and eukaryotes, by a delayed fluorescence method. Cyanobacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The use of cultured strains instead of natural seawater allows us to perform robust and controlled tests for the optimization of FCM. A previous study showed that B. prasinos NIES-2670 is sensitive to Zn, Pb, and Cu (Ota et al 2020); thus, it is an ideal representative test strain for analysis. Considering that previ- ous studies have applied the PI method to algae (Xiao et al 2011, Gumbo et al 2014, Nogueira et al 2015, Suman et al 2015, Zhang et al 2015, and the present validation experiment showed that damaged cells show enhanced yellow to orange fluorescence (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of cultured strains instead of natural seawater allows us to perform robust and controlled tests for the optimization of FCM. A previous study showed that B. prasinos NIES-2670 is sensitive to Zn, Pb, and Cu (Ota et al 2020); thus, it is an ideal representative test strain for analysis. Considering that previ- ous studies have applied the PI method to algae (Xiao et al 2011, Gumbo et al 2014, Nogueira et al 2015, Suman et al 2015, Zhang et al 2015, and the present validation experiment showed that damaged cells show enhanced yellow to orange fluorescence (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobium sp. NIES-981 is a PE-free cyanobacterium that has been used as a marine test strain (Yamagishi et al 2016, Ota et al 2020). In addition, the whole genome of this strain has been sequenced (Yamaguchi et al 2016), and the strain is used as a model alga in ecotoxicology studies.…”
Section: Validation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation